Historical and Political Background to the Erosion of the Rule of Law and Human Rights During Sri Lanka's Civil War and the Way Forward. (1st November 2016) - Deane, Tameshnie
Abstract: The Sri Lankan Civil War (1983–2009) is regarded as a violent reflection of deepening divides along political and ethnic lines. During this civil war the Sri Lankan Government and its security forces have been implicated in unlawful killings carried out in a pervasive manner against civilians, whilst at the same time specifically targeting ethnic Tamils, humanitarian workers and journalists. The human rights of all citizens suffered as a result and ultimately led to the weakening of the rule of law. With the end of the civil war, the Sri Lankan Government has made little progress in providing accountability for wartime abuses. Its absence of and reluctance to ensure justice is seen as a logical culmination of decades of impunity. The importance of acknowledging historical behaviour and taking accountability for past violations will be discussed. In an analysis for paving the way to a new democracy in Sri Lanka, the main outcomes of this article are calls for accountability arising out of the government's actions during the war; an investigation into the present state of human rights, the rule of law and finally; an examination into the political solution going forward to ensure a process of reconciliation and peaceful co-existence.